Policy in the South Cauсasus - V. A. Ponomarev (Проблемы постсоветского пространства)
The article examines the U.S. foreign policy in the South Caucasus at the present stage. Its main directions and features are highlighted. The article lays down the chronology of bilateral relations in the economic and military fields, as well as the U.S. policy of “democracy promotion” in the region. The current state of relations between the United States and the states of the South Caucasus is analyzed. The focus is on the policy of the Donald Trump administration in the region, as well as on the prospects of its implementation under the new Joe Biden administration.